Idealistic Modification of the Materialistic Veda - Khatri, Tilak Bahadur (Cognition, 2024)
This article explores the origin and the later developments of the Veda. The objective is to examine the materialist philosophical content of the early Vedas and contrast it with the idealistic readings of the text from later eras. This article discusses the research issues surrounding the historical roots of the Vedic literature and the idealistic changes made to it in later times. The study has used historical materialism as a methodological tool and examined several Vedic verses, relating them to the socioeconomic conditions of the period in which they were composed. The article has analyzed the roots of some terminologies frequently used in the text and their connections to the philosophy of the Veda. The terms bhagavan, rita, Dānam, Havana, Brahman, yajña and name of some gods are frequently used in the Veda and their meanings are analyzed in a particular historical contexts. The article reveals that the Vedic verses are the simple creations of Vedic Aryans and they are associated with the everyday desires of the Vedic people, such as those for food, cattle, rain, safety, prosperity, health, and progeny. The early creation of the Vedic verses are this-worldly and materialistic in content and they are in no way otherworldly and spiritualistic. The meaning of most of the terminologies found in the text has materialistic origin and in course of time, their meanings are converted into opposite. The philosophy of the Veda has its root in the collective mode of production and with the introduction of private property and classes, the text is made an ideological tool of the minority of governing classes. The Veda's original materialistic meaning is altered, and the book is transformed into a spiritual guidebook—an ideological weapon used by the ruling classes to deceive and repress the vast majority of laboring people.